A comparison of adverse reaction rates for PAS C versus plasma platelet units. Issue 8 (16th April 2014) - Cohn, Claudia S.; Stubbs, James; Schwartz, Joseph; Francis, Richard; Goss, Cheryl; Cushing, Melissa; Shaz, Beth; Mair, David; Brantigan, Barbara; Heaton, W. Andrew
<x xml:space="preserve">Abstract</x> Background Plasma constituents have been implicated in some types of platelet (PLT) transfusion reactions. Leukoreduced apheresis PLTs stored in InterSol have 65% less plasma than apheresis PLTs stored in 100% plasma (PPs). This study compared transfusion reaction rates in InterSol PLTs (PLT additive solution [PAS] C) versus PPs. Study Design and Methods The study design was an open‐label, nonrandomized retrospective review. Statistical methods were applied to substantiate noninferiority and superiority of PAS C compared to PP in terms of transfusion reaction rates. Adverse reactions (ARs) were categorized using the Biovigilance Component of the National Healthcare Safety Network. Active surveillance was used to monitor all transfusions, both with ARs and without ARs. Results A total of 14, 005 transfusions from six study sites were included, with 9845 PP transfusions given to 2202 patients and 4160 PAS C to 1444 patients. A total of 165 ARs were reported. Percentages of transfusions with ARs were 1.37% for PPs, 0.55% for PAS C, and 1.13% overall. The relative risk (RR) for PAS C versus PPs was calculated as 0.403 with an upper confidence limit (UCL) of 0.663. Overall, ARs with the highest incidence were allergic transfusion reactions (ATRs) and febrile nonhemolytic transfusion reactions (FNHTRs), at 0.66 and 0.40% of total transfusions reported, respectively. The relative risks (UCLs) for ATRs and FNHTRs, respectively, were 0.350 (0.686) and 0.336 (0.827). Conclusions PAS C PLTs were statistically superior and noninferior to PPs with respect to the transfusion‐related AR rate. PAS C noninferiority and superiority were also demonstrated for ATRs and FNHTRs, separately.